2020
DOI: 10.1016/j.oceaneng.2020.107943
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the coupled dynamic response of an offshore floating multi-purpose platform for the Blue Economy

Abstract: A multi-purpose platform is an offshore system designed to serve the purposes of more than one offshore industry. Within the context of "The Blue Growth Farm" project, an innovative multi-purpose configuration, comprising a wind turbine, wave energy converters, and an internal pool to accommodate aquaculture fish cages, has been proposed. The present work proposes a framework to assess the coupled dynamic response of the multi-purpose platform in realistic environmental conditions. A simplified parametric anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Food and energy are identified as sectors interested in an aquaculture strategy, also in the van den Burg et al (2019) paper that aims to contribute a systemic view of the marine sector boundaries and a methodology for innovative governance of the marine environment. The proposal of a multipurpose platform for evaluating marine environmental conditions is described in the paper of Li et al (2020) as a solution to the off-shore problems and configured to guarantee aquaculture and energy production. Implications of the blue economy and aquaculture in the food and energy areas are also provided by the paper of Fulton et al (2018).…”
Section: Geography Publication Networkmentioning
confidence: 99%
“…Food and energy are identified as sectors interested in an aquaculture strategy, also in the van den Burg et al (2019) paper that aims to contribute a systemic view of the marine sector boundaries and a methodology for innovative governance of the marine environment. The proposal of a multipurpose platform for evaluating marine environmental conditions is described in the paper of Li et al (2020) as a solution to the off-shore problems and configured to guarantee aquaculture and energy production. Implications of the blue economy and aquaculture in the food and energy areas are also provided by the paper of Fulton et al (2018).…”
Section: Geography Publication Networkmentioning
confidence: 99%
“…The cross section of the hull is Tshaped. This choice, based on extensive parametric studies, is aimed to: 1) enhance the natural periods of the vertical motions (Li et al, 2020b); 2) protect the inner moonpool; 3) promote modularity. The main characteristics of the platform are reported in Tables 1-3, with respect to dimensions, mass properties and mooring system, respectively.…”
Section: Full-scale Conceptmentioning
confidence: 99%
“…The aim of the two experimental campaigns is to provide pertinent experimental data, in particular with reference to the moonpool dynamics and the coupling effects of wind turbine, wave energy converters and fish cages. It is relevant to note that, in spite of the relatively large dimensions of the full-scale floating platform, hydro-elastic numerical analyses have shown that elasticity could be neglected for the assessment of the overall dynamics (Ruzzo et al, 2019;Li et al, 2020b). Therefore, physical models of the floating support platform have been designed as rigid bodies.…”
Section: Full-scale Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, a number of wave energy converters (WECs) have been designed and tested to date with varying degrees of success [1]. Among them, oscillating water columns (OWCs) have proved to be reliable, efficient and versatile, as they can be easily integrated into vertical breakwaters [2], or into floating multi-purpose platforms [3], thus reducing the associated construction cost. OWCs comprise a semisubmerged hollow chamber with a vertical opening located below the mean water level, which is exposed directly to sea waves.…”
Section: Introductionmentioning
confidence: 99%